Controllability of Nonlinear Fractional Delay Integrodifferential Systems - Nirmala, R. Joice; Balachandran, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we establish the sufficient conditions for controllability of nonlinear fractional delay integrodifferential systems. The results are obtained by using the solution representation of fractional delay differential equations and the application of Schauder’s fixed point theorem. Examples are provided to illustrate the results.